P111 Nurse specialist led sleep pathway is clinically and cost effective compared to a pathway delivered by consultants. (11th November 2022) - Darda, M; Ward, L; Devasia, S; Pratley, W; Bloxham, S; Cooke, D; Pittman, MA
Abstract : Introduction: The merger of two similar hospitals but with very different sleep pathways allowed a comparison, particularly of the use of Clinical Nurse Specialists (CNS) on one of the sites. Methods: A retrospective study was conducted on patients set up on CPAP on the two sites, sampled from August to December 2018; allowing a reasonable follow up period before the covid pandemic started. Data were collected on time from referral to CPAP set up, severity, patient outcomes, and approximate costs of the variable parts of the pathways. A total of 132 episodes were investigated. Results: All patients on the consultant led site saw a consultant at least once and were all given an autoset device. None of the patients on the CNS led site required a consultant appointment, and only one was given an autoset device, the rest receiving a fixed pressure machine. This resulted in significant differences in set up costs between the two sites. The use of CNS significantly reduced waiting times by expanding the number of new appointments available. Compliance hours and change in Epworth score were comparable between the two sites. The number of patient visits on the consultant led site was higher than the CNS led site. Interestingly severity was significantly higher on the CNS site, however a number of patients on the consultant site were given CPAP on the basis of an essentially normal oximetry, but with compelling symptoms which may explain at least part of this difference. Mean CPAP pressure used was significantly lower on the CNS site, which predominantly relied on fixed pressure machines, however as the compliance hours and change in Epworth sleepiness scale were not significantly different, this does not suggest undertreatment in this group. BMI was not different in the two patient groups, and thus does not explain the differences seen in severity or CPAP pressure. Conclusions: CNS led sleep clinics increase capacity and reduce costs compared to consultant led ones, without negatively impacting patient outcomes. The use of autoset devices did not significantly influence compliance and sleepiness compared to fixed pressure machines in this study.